Entrepreneurship versus joblessness: Explaining the rise in self-employment - Paolo Falco; Luke Haywood (Journal of Development Economics, 2016)
A large share of the workforce throughout the developing world is self-employed, and this proportion has increased in recent decades. Assessments of this development vary, with pull factors such as high returns to capital contrasted with push factors such as barriers to more desirable salaried jobs. Using a long panel dataset from Ghana, we empirically investigate the changing structure of earnings in self-employment relative to salaried work. Our analysis allows workers to sort into self-employment for different reasons, including expected earnings differentials and endogenous capital accumulation whilst highlighting constraints that workers may face. We estimate a correlated random coefficient model using IV-GMM, taking into account the endogeneity of sector choice and capital accumulation. We find that returns to productive characteristics in self-employment have increased significantly between 2004 and 2011 whilst self-employment has attracted increasingly skilled workers. This points against the negative view of self-employment as an occupation of last resort.
Keywords: 330; Self-employment; African labour markets; Semiparametric models; Comparative advantage; Segmentation